Structuring of Statutory Values of Polish Tax Procedures - Gorgol, Andrzej (Review of European and Comparative Law, 2021)
This paper aims to provide a critical analysis of the regulation of statutory principles of tax proceedings under a preliminary assumption that the values of Polish tax procedures shall reflect the general determination of the legal system. An attempt was made to demonstrate that the structuring of axiology of these procedures does not fully account for this constitutional requirement.